Pelatihan serta Bimbingan Guru Sekolah Dasar dalam Menyusun Materi Pelajaran Seni Budaya dan Prakarya pada Kurikulum Merdeka Belajar - Yona Syaida Oktira; Kristian Burhan; Helfany Amsa (Yayasan REDI Tiga Monas, 2023)
Training for arts and culture and crafts subjects in elementary schools aims to gain and share knowledge with teachers and students. The problem encountered is that teachers only use the lecture method, with this activity teachers are free to use any methods, models, media and strategies for the learning process. This activity aims to: (1) so that teachers increase their knowledge regarding the independent learning curriculum, especially in Arts, Culture and Crafts subjects in elementary schools, (2) so that teachers have various teaching methods in Arts, Culture and Crafts subjects, (3) exchange ideas with the school on Arts, Culture and Crafts subjects so that the learning process runs smoothly, what needs must be provided by the school, and (4) guiding teachers to prepare materials with the aim of creating the latest student worksheets and the latest modules for arts, culture and crafts subjects . With this training, teachers better understand what steps must be taken to add ideas, change the mindset that the independent learning curriculum is not difficult. It's just that the method is slightly differentiated so that competency is achieved and learning evaluation improves and it is easy to foster students' interests and talents. The method used is a qualitative method with a participatory approach with preparation, implementation and evaluation stages. The expected results in this community service activity are that teachers are able to prepare arts and culture materials and crafts according to curriculum needs and teachers are able to stimulate interest and talent in the arts and culture and crafts learning process in elementary schools.